Breast cancer in men. Case report - Bombón-Caizaluisa, Marco Fabricio (2024)
Introduction: Male breast cancer is an infrequent pathology; it represents less than 1% of malignant breast pathology, with an average age of diagnosis of 67 years. It has a worse prognosis than female breast cancer, due to its high genetic origin and low suspicion, which leads to inadequate and late diagnosis, becoming evident in advanced stages, decreasing survival in the medium and long term. Objective: To describe the clinical case of a patient diagnosed with breast cancer, addressing the clinical presentation, diagnostic methods, oncospecific treatment, as well as the corresponding clinical and surgical evolution. Case presentation: We present a 52-year-old male patient, with evidence of exophytic lesion in right breast plus ipsilateral axillary node, with diagnosis confirmed by pathology report of breast cancer, clinical stage: cT4bN1Mx. A multidisciplinary management is proposed, initially the patient receives neoadjuvant chemotherapy, then undergoes a surgical procedure: radical right mastectomy. Finally, she receives oncospecific treatment in the specialties of clinical oncology and radiotherapy, with favorable evolution. Discussion: Male breast cancer has a low incidence compared to women, so its diagnostic suspicion is limited. In initial stages the diagnosis is unspecific due to the few clinical manifestations, but should be supported by imaging methods and confirmatory methods, an anatomopathological and immunohistochemical analysis, to guide oncospecific treatment. Conclusions: Male breast cancer, is an infrequent pathology with limited diagnostic suspicion, which requires specific multidisciplinary management. It is important to have a continuous medical follow-up of the patient, to achieve at the time of diagnosis a correct clinical and immunohistochemical staging, which allows to focus on the appropriate management and treatment, with better clinical outcomes and better survival rates